Peranan Perbankan Syariah Dalam Pemberdayaan UMKM Sebagai Upaya Peningkatan Kualitas Hidup Masyarakat Kota Salatiga - Anwar Rosidi; Heru Prastyo; Edwin Zusrony (ITB AAS INDONESIA Surakarta, 2021)
This research technique uses interviews. Interviews were conducted with several UMKM in Tingkir Lor Village who are customers in Islamic Banking, and 1 (one) mantri at Bank Muamalat KCP Salatiga. However, in this study, the researcher will also use the literature study method or the method of using document materials, because the researcher does not directly examine and process the data obtained from the respondents themselves but examines and copies the data or documents produced by other parties. In addition to supporting the results of the interview, it is also used to describe in general the real role of Islamic banking towards UMKM.